Is there economic convergence in Asia? - Dante B. Canlas (University of the Philippines, School of Economics (UPSE), 2020)
This paper opens up a study of economic convergence in Asia. This convergence refers to the ability of developing economies to catch up with the developed ones in terms of levels and growth rates of real per capita GDP. The study uses the lens of neoclassical growth models, both the basic models of Robert Solow and Trevor Swan, along with the models of Robert Lucas Jr. and Paul Romer in endogenous growth theory to interpret observed growth in Asia. Data are taken from the 45 developing member countries of the Asian Development Bank. The study supports conditional convergence but not absolute convergence. That is the lagging economies can catch up with the leading economies provided the former can adopt advanced technologies, such as, those that feature human-capital investments, learning-by-doing and increasing returns from knowledge accumulation.
Keywords: N15; O11; O42; 330; economic convergence; neoclassical growth models; Asia